Survival is predicted by territorial status but not wing pigmentation in males of a polythorid damselfly, Euthore fasciata (Odonata: Zygoptera: Polythoridae) (2020)
Robust male condition must be favored and should be signaled to conspecifics via enhanced aggression and more highly expressed ornamental traits. One way that such robust condition, and thereby the expression of aggression and ornamental traits, can be assessed is via survival. In odonate adults, condition (in the form of lipid reserves, muscle mass and immune ability) has been correlated with the expression of: (a) territorial behavior (as opposed to nonterritorial, satellite behavior), and (b) larger wing pigmentation patterns. In the present work, we investigated these two patterns using adult males of Euthore fasciata in a field study. Males bear black and white pigmented wing patterns and express territorial and nonterritorial behaviors to secure matings. We predicted that, due to their better condition, territorial males should have higher survival and larger pigmented patterns than nonterritorial males, and that larger pigmented patterns would correlate positively with survival. We marked–recaptured males, measured their pigmented patterns and recorded their behavior. Our results indicated that territorial males (n = 12) had a higher survival, but not larger pigmented areas, than nonterritorial males (n = 39), and that there was no significant relationship between wing pigmentation and survival. This result confirms that territorial males are in better condition than nonterritorial males. However, wing pigmentation does not seem to signal such condition to conspecifics although the reduced number of animals may have affected our analysis. Tentatively, the assumed relationship pigmentation/condition cannot be generalized in odonates.